Shaky foundations: Policy lessons from America's historic housing crash - Pedro Nicolaci da Costa (Levy Economics Institute of Bard College, 2008)
A bursting asset bubble inevitably requires central bank action, usually when it is already too late and with adverse spillover effects. In this sense, the Federal Reserve and other central banks already target asset prices; yet, by taking aim at them only on the way down - as in the current housing and credit crisis - the Big Banks create a self-perpetuating cycle of perverse incentives and moral hazard that often gives rise to yet another round of bubbles. The US central bank's current premise is that policymakers cannot and should not target asset bubbles. However, the housing story has rendered untenable the prevailing belief that bubbles are impossible to spot ahead of time. The warning signals were ubiquitous - for example, price charts showing home values rising impossibly into the stratosphere, and Wall Street's increasing reliance on housing-backed bonds for its record-setting profits. It has become abundantly clear that there was plenty the Fed could have done to discourage speculative behavior and put a stop to predatory lending. Recent US experience has bolstered the view that asset prices must come under the central bank's purview in order for the economy to retain some semblance of stability. Former Fed Chairman Paul Volcker recently called for a broader regulatory role for the central bank in light of the housing-centered credit crisis. Indeed, Treasury Secretary Henry Paulson's latest plan for tackling the crisis involves giving the Fed vast new authority to regulate investment banks, not just depository institutions. However, news analyst Pedro Nicolaci da Costa argues that attitude changes among regulators will be even more important than shifts in mandate in ensuring that regulators like the Fed do their jobs properly.
Keywords: 330; Wohnungsmarkt; Finanzmarktkrise; Subprime-Hypothek; Börsenkurs; Bubbles; Wertpapierspekulation; USA